Only Connect - Robert Mighall (LID Publishing)
A coherent story can make you better understood, believed in and trusted. So why is the business world only just discovering its power? This book draws on the psychology, history, and of course, the greatest works, of storytelling to show how modern businesses can communicate more effectively and creatively. Robert Mighall explains why story has a universal power to move people. He shows how to build a compelling core story, and apply that across a range of communications. And he demonstrates how trends in social media and content marketing are making this most ancient communication art ever more urgently relevant. What the corporate world needs most, story does best: establish the human connections upon which trust is build. And this book explains how.